High pCO2 promotes coral primary production. (26th July 2019) - Biscéré, T.; Zampighi, M.; Lorrain, A.; Jurriaans, S.; Foggo, A.; Houlbrèque, F.; Rodolfo-Metalpa, R.
Abstract : While research on ocean acidification (OA) impacts on coral reefs has focused on calcification, relatively little is known about effects on coral photosynthesis and respiration, despite these being among the most plastic metabolic processes corals may use to acclimatize to adverse conditions. Here, we present data collected between 2016 and 2018 at three natural CO2 seeps in Papua New Guinea where we measured the metabolic flexibility (i.e. in hospite photosynthesis and dark respiration) of 12 coral species. Despite some species-specific variability, metabolic rates as measured by net oxygen flux tended to be higher at high p CO2 ( ca 1200 µatm), with increases in photosynthesis exceeding those of respiration, suggesting greater productivity of Symbiodiniaceae photosynthesis in hospite, and indicating the potential for metabolic flexibility that may enable these species to thrive in environments with high p CO2 . However, laboratory and field observations of coral mortality under high CO2 conditions associated with coral bleaching suggests that this metabolic subsidy does not result in coral higher resistance to extreme thermal stress. Therefore, the combined effects of OA and global warming may lead to a strong decrease in coral diversity despite the stimulating effect on coral productivity of OA alone.